(untitled) (Global Journal of Management and Business Research, 2014)
Employees are regarded as a most valuable resource and the main driver for organizational success. In order to be successful, an organization needs to consistently motivate employees so that they can act toward the goals of the organization and have a strong desire to remain in the organization. This study attempted to draw influences of different motivational factors such as salary adequacy, future security, social dignity/status, career ambition, training and development, comfortable physical environment,